A refractive index sensor based on micro-nano fiber with chirped fiber Bragg grating embedded for a microfluidic chip - Xie, Zhanwu; Yan, Haitao; Li, Pengfei (Oficyna Wydawnicza Politechniki Wrocławskiej, 2023)
A refractive index (RI) sensor based on micro-nano fiber (MN-fiber) with chirped fiber Bragg grating (CFBG) Fabry–Perot cavity (FP-cavity) for a microfluidic chip has been proposed. A single-mode fiber is drawn by hydrogen flame heading come into MN-fiber. Two CFBGs are written into this MN-fiber by the ultraviolet (UV) laser mask exposure method. One is at the tapered region, another is at the micro-nano region. Then a micro-nano fiber with chirped fiber Bragg grating (MN-CFBGs) FP-cavity sensor is formed. The Bragg reflection wavelengths of two CFBGs are 1620 nm, 3-dB bandwidth are above 50 nm. The reflectance of two CFBGs are 70% and 99%, respectively. The effects of reflectivity and bandwidth of the CFBGs FP-cavity, diameter and length of MN-fiber with this sensor’s optical properties are analysed is and discussed. This sensor is embedded in a microfluidic chip and the MN-fiber region is immersion microfluid in different channels. The experimental results show that refractive index sensitivity of the sensor is –986 nm/refractive index unit (RIU), and the signal of the sensor has little noise. The CFBG-FP sensor not only has high sensitivity and lager measurement range, but also high contrast resonance signal and stability.
Optica Applicata, Vol. 53, 2023, nr 4, s. 633-642
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; micro-nano fiber; chirped fiber Bragg grating; Fabry–Perot cavity; microfluidic chip; sensor